American Women’s Experiences With Intimate Partner Violence during the Start of the COVID-19 Pandemic: Risk Factors and Mental Health Implications - Oswald, Debra L. (Violence against women, 2023)
In an online survey, women self-reported high prevalence of intimate partner violence during the early days of the pandemic. Risk factors for experiencing intimate partner violence (IPV) included having a child under the age of 18, being a sexual minority, living in a rural community, and stressors related to healthcare access, income/employment stress, and COVID-19 exposure or illness. Women who worked during the pandemic and were older were less likely to experience IPV. Women who reported IPV also reported increased anxiety and depression. The results are discussed in terms of clinical and policy implications for supporting women who are victims of IPV.